Lifestyle Practices and Its Influence on Quality Of Life among Breast Cancer Survivors. - Najwa Haneem Mohamad; Zoharah Omar; Nor Aina Emran (Universiti Kebangsaan Malaysia, 2014)
Breast cancer is ranked number one from the ten most frequent cancers in female, Peninsular Malaysia. Various studies provide negative evidence on malignancies and one of the end results is impaired quality of life (QOL). Studies show lifestyle approaches are key factors in enhancing the QOL among cancer survivors. The purpose of this study is to describe the lifestyle practices (LP) among breast cancer survivors (BCS) which consist of dietary intake, exercise habits, and stress management and to determine whether these practices have influence on the QOL among Malaysian BCS.